2011
DOI: 10.1016/j.lwt.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Development of a quality index method (QIM) sensory scheme and study of shelf-life of ice-stored blackspot seabream (Pagellus bogaraveo)

Abstract: a b s t r a c tThe aim of this work was to develop a quality index method (QIM) scheme for whole ice-boxed refrigerated blackspot seabream and to perform shelf-life evaluations, using sensory analysis, GR Torrymeter measurements and bacterial counts of specific spoilage organisms (SSO) during chilled storage. A QIM scheme based on a total of 30 demerit points was developed. Sensory, physical and microbiological data were integrated and used to determine the rejection point. Results indicated that the shelflife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
3
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 30 publications
4
63
3
8
Order By: Relevance
“…and S. putrefaciens have been reported as the SSB, regardless of the origin of the fish in temperate and tropical waters (Gillespie 1981;Lima Dos Santos et al 1981;Gram and Huss 1996), and in fresh Mediterranean fish stored aerobically under refrigeration (Koutsoumanis and Nychas 1999) or ice storage (Gennari and Tomaselli 1988;Gennari et al 1999;Sant'Ana et al 2011). The values of S. putrefaciens showed in our study were lower than those observed for Pseudomonas sp.…”
Section: S Putrefaciens Pseudomonas Spcontrasting
confidence: 54%
“…and S. putrefaciens have been reported as the SSB, regardless of the origin of the fish in temperate and tropical waters (Gillespie 1981;Lima Dos Santos et al 1981;Gram and Huss 1996), and in fresh Mediterranean fish stored aerobically under refrigeration (Koutsoumanis and Nychas 1999) or ice storage (Gennari and Tomaselli 1988;Gennari et al 1999;Sant'Ana et al 2011). The values of S. putrefaciens showed in our study were lower than those observed for Pseudomonas sp.…”
Section: S Putrefaciens Pseudomonas Spcontrasting
confidence: 54%
“…and S. putrefaciens have been reported as for SSB in fish from temperate and tropical waters (Gillespie, 1981;Lima Dos Santos et al, 1981;Gram and Huss, 1996) and in fresh Mediterranean fish stored aerobically under refrigeration (Koutsoumanis and Nychas, 1999) or ice storage (Gennari and Tomaselli, 1988;Gennari et al, 1999;Sant'Ana et al, 2011). The values for S. putrefaciens reported in this study were lower than those observed for Pseudomonas spp.…”
Section: (2009) Other Authors Described Higher Initial Counts Ofcontrasting
confidence: 46%
“…The QI assessment was done as recommended by Sant'Ana et al (2011). The trained jury consisted of 10 (ten) people, 5 men and 5 women, selected by their experience in sensory analysis of fish.…”
Section: Methodsmentioning
confidence: 99%